2022
DOI: 10.3389/fimmu.2022.940929
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Changes in Growth Performance, Antioxidant Capacity, Immune Response, Hepatic Health, and Flesh Quality of Trachinotus ovatus Fed With Oedocladium carolinianum

Abstract: The purpose of this study is to assess the feasibility of astaxanthin-rich Oedocladium carolinianum as an immunostimulant in the diet for Trachinotus ovatus. Three experimental diets containing 0% (OC0), 1% (OC1), and 5% (OC5) O. carolinianum powder were formulated for 6-week feeding trials. The results indicated that the OC5 diet boosted the growth performance through decreasing the feed conversion ratio and increasing digestive enzyme activities and intestinal villus length. Meanwhile, fish fed with the OC5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Thus, digestive function is closely correlated with intestinal development [ 34 ]. Earlier studies reported that an increase in villi length and villi thickness implies an enlargement of the surface area and, consequently, improved absorption of nutrients [ 14 , 35 ]. Muscular thickness is closely correlated with the peristaltic capacity of the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, digestive function is closely correlated with intestinal development [ 34 ]. Earlier studies reported that an increase in villi length and villi thickness implies an enlargement of the surface area and, consequently, improved absorption of nutrients [ 14 , 35 ]. Muscular thickness is closely correlated with the peristaltic capacity of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals that dietary astaxanthin down-regulates the activity of ALT and AST in plasma, which is consistent with previous observations in other fish species fed on diets supplemented with different sources and concentrations of astaxanthin [ 46 , 48 ]. It is noteworthy that fish in aquaculture are sensitive to environmental stressors and infections [ 14 ]. Accordingly, supplementing fish feed with astaxanthin is considered helpful in relieving environmental stress and protecting the liver, in turn improving fish health in cage culture [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of antioxidant parameters and gene expression [22]. Besides, from three fish randomly chosen from each cage, the liver was removed and fixed in 40 g/kg paraformaldehyde solution (Servicebio Technology Co., Ltd., Wuhan, China) for histological analysis.…”
Section: Fish Andmentioning
confidence: 99%